The Concept of Public Interest Litigation in India: A Dynamic Approach - Baisoya, Amit (Trinity Law Review, 2024)
Public Interest Ligation is that the public in general are interested in exoneration of some right or enforcement of some public duty. Such litigation has hitherto been entertained by Supreme Court under article 32 and by High Court under article 226 of the constitution of India not only from association or organization by also from individual in a common cause. The Public Interest Litigation Regulation Bill, 1996, Introduced in Parliament by Sri Suresh Pachuri as a private Bill was one such effort. After discussion, the bill lapsed. While there was difference with in parliament on this, the judiciary also felt that PIL was useful and that the judiciary could regulate and monitor PIL and prevent its misuse. In matter where the Legislature and the Executive fell short of their roles, the PIL could be very useful. In matters relating to the environment and poor, unorganized people and also where enlightened citizens took up important social issue, PIL is very important. It provides one more forum for social justice. Though certain sections are against it, and they have generally vested interest, PIL provided much relief too many sections of the people on several issues of importance. Hence, in spite of some opposition, it has become to be an important pillar of India Judicial system and it continues to grow nationally in Importance. I have discussed and explained in this paper meaning, nature and scope of PIL.I have explained also principles evolved by Supreme Court for PIL, misuse or abuse of PIL. Besides, I have explained social dimension of PIL.